PERAN BAHASA DALAM KESEHATAN MENTAL DI LINGKUNGAN KERJA - Deden Novan Setiawan Nugraha; Puspita Sari; Susiyanti Susiyanti; Hero Gunawan; Dianita Dianita; Ervina CM Simatupang (LPPM Universitas Bina Bangsa, 2024)
This Community Service (PKM) activity was carried out to provide understanding and knowledge to the staff of Courtyard by Marriott Bandung Dago Hotel about the Role of Language in maintaining Mental Health in the Work Environment. The methods used in PKM are lectures, discussions, and exercises. The results of the activity showed that, of the 23 participants who were staff of Courtyard by Marriott Bandung Dago Hotel, 14 (61%) people were experiencing low burn out, 7 people (31%) were experiencing moderate burn out, and 2 people (9%) were experiencing high burn out. As for after receiving the material presentation, as many as 83% of participants stated that they had understood the material presented. In addition, participants also assessed that they had gained additional insights and new information about the role of language in maintaining mental health in the work environment